EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN THINK PAIR SHARE (TPS) PADA MATERI ALJABAR DITINJAU DARI KECERDASAN LOGIS MATEMATIS SISWA KELAS VII SMP NEGERI SE-KOTA SURAKARTA TAHUN PELAJARAN 2015/2016 - Ayuningrum, Retna; Budiyono, Budiyono; Slamet, Isnandar (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objectives of this research were to find out: (1) which one learning model that provide better mathematics learning achievement, TGT learning model, TPS learning model, or direct learning model, (2) which one category logical matematical intelligence of students that giving better mathematics learning achievement, high, medium, or low, (3) in each category logical matematical intelligence which one providing better mathematics learning achievement, TGT learning model TPS learning model, or direct learningÂ  model. (4) in each learning models which one providing better mathematics learning achievement category self confidence high, medium, or low. The type of this study was a quasi-experimental study with a 3x3 factorial design. The population was all grade VII students of Junior High Schools in Surakarta Regency in the school year of 2015/2016. Population of this research was all VII graders of Junior High School of Surakarta. The samples of the research were taken by using the stratified cluster random sampling. The sample consisted of 291 students: 96 students for experiment I class, 97 for experiment II class and 98 for control class. The instruments used for the data collection were mathematics achievement test and logical mathematical intelligence The data analysis technique used was unbalanced two ways analysis of variance. Based on the hypotheses, the results of the study can be summarized as follows: (1) The use of TGT resulted better achievement than that of TPS and direct learning model, the use of TPS resulted better achievement than that of direct learning model. (2) The studentsâ achievement who have high logical mathematical intelligence was better than those who have middle or low logical mathematical intelligence, and students who have middle logical mathematical intelligence were better than those who have low logical mathematic intelligence.Keywords: TGT,TPS, Direct Learning, and Logical Mathematical Intelligence.